Synthesis of Enantiomerically Pure α-Hydroxylated Nervonic Acid – A Chiral Pool Approach to α-Hydroxylated Unsaturated Fatty Acids - Pawliczek, Martin; Wallbaum, Jan; Werz, Daniel B. (Synlett, 2014)
A scalable and robust synthesis to α-hydroxylated nervonic acid is presented. The chiral-pool approach starts with malic acid and employs only highly reliable reactions such as Wittig reactions, protecting group conversions, and reductions. Depending on the configuration of malic acid being used as starting material both enantiomers can be obtained.
Keywords: lipids; fatty acids; malic acid; nervonic acid